The flow of financial resources to less-developed countries, 1956-1963 - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1963)
This contains the fourth report in the series published by the O.E.C.D. and its predecessor the O.E.E.C on the flow of financial resources to developing countries. The report are intended to provide factual information about the flow of financial resources reported by individual donor countries and by the multilateral agencies.
Includes bibliographic references
usc 26/09/18
Loans
Keywords: Finance; Economic assistance